Error compensation of grating interferometer due to angular error of linear stage - Zhang, Y. L. (2013)
Linear Diffraction Grating Interferometer (LDGI) is a long stroke and nanometer resolution displacement sensor for any linear stages. The principle of this diffractive interferometer is based on the Littrow configuration and phase information encoded by the ±1st order beams diffracted by a holographic grating. Because the emitted beams are separated on the grating plane, the yaw error of the stage during motion will cause the optical path difference of the two beams resulting in phase shift. This study investigates the influence of the yaw error. Experiments show that after yaw error compensation, the LDGI readings can be significantly improved.